Vulnerability to food insecurity and coping strategies of agrarian households in the lower river region of the Gambia: Implication for policy - Josephine Mendy; Godswill Azinwie Asongwe; Raymond Ndip Nkongho (International Journal of Agricultural Science and Food Technology - Peertechz Publications, 2020)
This study assessed the extent of agrarian households' vulnerability to food insecurity and coping strategies in the Lower River Region of The Gambia and implication for policy. The data was collected principally through questionnaires administered to 230 households and 10 key informants. Data was analysed using descriptive statistics with the aid of Statistical Package for Social Science 20. A modified Consolidated Approach to Reporting Indicators (CARI) was also used to analyse vulnerability to food insecurity in the study area. The study found out that on average, the degree of vulnerability to food insecurity in the study area is about 45%. Vulnerability to food security is partly due to the large sizes of families, low income level of households, limited access to land and limited availability of food due to low food production, droughts and extreme climatic conditions. About 1,309 households were found to be highly vulnerable, and 4,394 households moderately vulnerable. Among the different districts in Lower River Region, the majority of the food insecure households are located in Jarra West District. As a coping strategy, 65.3% to food insecurity households, tend to reduce their expenditures on other needs to have money to buy food, 53.7% turn to the consumption of low quality and cheaper foodstuff with high carbohydrate content like rice, 52.1% borrow food from relatives, friends and neighbours and 51.3% reduce adults' food consumption to secure the need of children for food in times of food deficit. Weak institutional and governance capacity, as well as unsustainable and inequitable use of natural resources among others were identified as common drivers of protracted crises. The study concluded that the trends in food security and nutrition in The Gambia are intrigued by climate variability and vulnerability to shocks and crises. To reduce food insecurity among vulnerable populations, special subsidy packages should be designed to ease access to farm inputs, to better manage risks and respond to shocks in the short and long term. The government should also provide a regulatory environment which establishes basic conditions within which farmers, input suppliers, and food companies, among others can operate and make investment decisions in order to boost their production. The managerial and technical capacity of these farmers should also be built through the extension services, and the extension services should work with farmers to achieve the national priority of zero hunger. The government should reduce the amount of taxes levied on companies that produce or import quality planting materials and inputs and then negotiate with these companies to step down the cost of inputs to farmers. There is also a need for the introduction of new, appropriate and sustainable technologies to farmers and for intensification purposes.